Financing Education: A Route to the Development of a Country - Bhuiyan, Abdullah Al Mamun (Universitas Negeri Semarang, 2019)
Everybody knows that education is the backbone of a nation. The countries which have realized that motto and invested a lot for a long time for sustainable development of the education sector of the country, they are now forerunner in innovation, world influence, employment, innovative thinking, world-class health care service, technology, ideological influence and even military advancement. They have diversified education investments which have had defused the progress in all sectors. On the contrary, there are many countries which are wealthier than many developed countries, but for creative ideas, educational advancement, climate change and even for major decisions, they rely on some specific advanced countries. These countries cannot ensure sustainable development of their own as they rely on others. Besides, some countries mostly depend on natural resources which are now facing constraint for plummeting of the price of those assets due to worldwide economic depression or the invention of alternative option. The countries which have the best education in the world, they have more researchers and diversified world-class education system and creativities to cope up with the changing world circumstances. Therefore, education financing opens up a variety of employment opportunities which leads to the reduction of the crime rate of a countryÃ¢â‚¬â€consequently, leads to the sustainable economic development of a nation.